Management communication methods and employee commitment to organisational change: a qualitative analysis of an international consumer goods company - Frost, James (2022)
Organisations frequently struggle to manage change successfully. Effective management communication during change is directly linked to successful and long-term organisational change through employees’ commitment to change. This qualitative study explores the relationship between management communication and commitment to change from the perspectives of 13 employees at the middle management level of the northern European division of an international consumer goods company. Reflexive thematic analysis was utilised to analyse data from a series of 13 semi-structured interviews. The research questions of the study are focused on three primary areas to investigate: how employees perceive the effectiveness of the management communication methods utilised during organisational change, the ways in which employees believe that management communication methods affect their commitment to change, and how employees believe that employers could improve their commitment to change. The findings of the study highlight the critical importance of active participation, consistency, frequency, and face-to-face opportunities within management’s communication of change in order to generate affective commitment to change within middle managers. This provides an important contribution to the existing literature; the relationship between management communication and middle managers’ commitment to change during the implementation phase of change has received inadequate attention in existing research.